(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In the modern era, burnout has emerged as a major psychosocial workplace risk that has a substantial financial impact on both individuals and companies [5, 9, 11]. Nurses who are burnt out are less committed to the organisation, have worse quality of life, and are more likely to want to quit. Furthermore, burnout lowers nursing care quality and raises turnover rates.